40 Gbit/s waveguide photodiode using III-V on silicon heteroepitaxy - Sun, Keye; Gao, Junyi; Jung, Daehwan; Bowers, John; Beling, Andreas (OPTICAL SOC AMER, 2020)
Low-dark-current waveguide modified uni-traveling carrier photodiodes (PDs) are demonstrated by direct heteroepitaxy of InGaAs/InAlGaAs on silicon templates. The PDs have a dark current of 0.1 mu A at -3 V bias and an internal (external) responsivity of 0.78 A/W (0.27 A/W). The 3 dB bandwidth is 28 GHz, and open eye diagrams are detected at 40 Gbit/s. (C) 2020 Optical Society of America
Keywords: HIGH-POWER; AVALANCHE PHOTODIODES; PHOTODETECTOR